Cryogenic two-photon laser photolithography with SU-8 - Lee, K; Green, A; Taylor, R; Sharp, D; Turberfield, A; Brossard, F; Williams, D; Briggs, G (2006)
We have shown that photolithography can be used to create alignment markers on a semiconductor substrate at cryogenic temperatures. The epoxy resist SU-8 can be exposed effectively by two-photon absorption at a temperature of 4 K. By this means a spectroscopy apparatus can be used to find the positions of randomly distributed structures at low temperatures, such as InGaAsGaAs quantum dots, and mark their positions. We present a systematic study of the optical exposure parameters for cryogenic two-photon laser photolithography with SU-8. © 2006 American Institute of Physics.